Food intolerance and the food industry - Dean, Taraneh (CRC Press ; Woodhead Pub., 2000)
This book provides food industry professionals with information on food intolerance, including its diagnosis, symptoms, and management. Covers issues such as the handling of allergenic food in retail and manufacturing as well as applicable legislation.
Keywords: Food intolerance.; Food -- Toxicology.; Food handling.; Nutrition disorders.; Food industry and trade.; Food -- Labeling.; Food allergy.; elektronické knihy; electronic books